2019
DOI: 10.1371/journal.pone.0222171
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic microbiota profiling in fecal samples depends on combination of sequencing depth and choice of NGS analysis method

Abstract: The human gut microbiota is well established as an important factor in health and disease. Fecal sample microbiota are often analyzed as a proxy for gut microbiota, and characterized with respect to their composition profiles. Modern approaches employ whole genome shotgun next-generation sequencing as the basis for these analyses. Sequencing depth as well as choice of next-generation sequencing data analysis method constitute two main interacting methodological factors for such an approach. In this study, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
(69 reference statements)
2
11
0
Order By: Relevance
“…The last of the applied methods, i.e., next-generation sequencing, definitely brings the most abundant data, considering the bacterial diversity of the intestinal microbiota. The weakness of this method, however, is that the results are relative; we do not have absolute numbers of individual genera and the bacteria represented in a very low titer may be underrepresented in the sample [ 38 ]. Keeping in mind that this is a semi-quantitative method, not a quantitative one, and inferences based on the indicated percentages must be careful, we can see the differences that we observed between donor C and donors A and B may point to unique combinations of individual species.…”
Section: Discussionmentioning
confidence: 99%
“…The last of the applied methods, i.e., next-generation sequencing, definitely brings the most abundant data, considering the bacterial diversity of the intestinal microbiota. The weakness of this method, however, is that the results are relative; we do not have absolute numbers of individual genera and the bacteria represented in a very low titer may be underrepresented in the sample [ 38 ]. Keeping in mind that this is a semi-quantitative method, not a quantitative one, and inferences based on the indicated percentages must be careful, we can see the differences that we observed between donor C and donors A and B may point to unique combinations of individual species.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the data obtained from these primers and MPS suggest they may be used as classifiers [ 43 ] to reveal the background bacteria of a sample, but the application may be limited depending on the data in the 16S rRNA gene database. Variation in the number of species reported by different methods could be attributed to both the differences in the taxonomy assignment strategy and the reference databases used by the methods [ 13 ]. It is likely that our 16S rRNA gene-targeted primers, in combination with MPS, can be used to detect bacteria from complex samples, as evidenced by testing with an environmental background.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, after sample processing, the generated data are compared to a database to facilitate taxa identification [ 11 ]. Hugenholtz et al [ 12 ] showed that two or more 16S rRNA gene hypervariable regions could provide the phylogenetic division of microorganisms into monophyletic groups depending on the reference database and the different choices of classification [ 13 ]. Nevertheless, microbial composition data differ depending on the primers and sequencing platforms used [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that a sequencing depth of 0.5 M sequences per sample is sufficient to capture taxonomic and functional signals on par with those obtained with sequencing depths > 100 M sequences [ 3 , 10 ]. Other studies using reference materials have also found that taxonomic classification does not necessarily improve beyond 60 M paired sequences, and classification of eukaryotic communities can be estimated with 0.5 M reads [ 11 , 12 ]. Shallow SMS (SSMS) has recently emerged as a cost-effective and information-rich alternative to SMS and 16S sequencing [ 3 ].…”
Section: Introductionmentioning
confidence: 99%